Concerns of Forensics Expertise in Ophthalmology - Mirjana A Janicijevic-Petrovic; Nenad, Petrovic; Janicijevic, Katarina; Popovic, Andrijana (International Journal of Medical Research, 2013)
Professionally competent and sworn to court experts - ophthalmologists, for the society recognized as permanently licensed court experts, stand advised in front of the face of medical justice (Hippocratic Oath), with their expertise and knowledge, scientific research in their domain, empirical doctrine and practice, to put the findings and opinion to put conscientiously in court, in accordance with the rights and obligations of medicine and science. Classification of eye injury is defined as heavy or light, without the possibility of categorizing moderate heavy or moderate light injuries and eye diseases. Reduction of environmental activity (ability) - experts should elaborate to the judgment, about the final treatment, permanent sequels, and for certain types of work, activities (work capacity), for which persons are fully or partially capable of performing, or are not in a condition because of causal reasons. According Legislation concept of pain occurs in the form of emotional, and the degree and duration of physical pain, which is causally related to trauma and / or diseases of visual equipment. Court practice has graded entity of disfigurement as disfigurement, cosmetic alterations medium level of cosmetic defects and light degree. Concerns of ophthalmic expertise show that it is necessary to harmonize, to suggest recommendations and guidelines for this complex work so that forensic expertise can become even bigger challenge placed in front of an ophthalmologist, and more effective health and long benefit of patients.